Psychometric-Based vs. Proof Pass Rate Metrics in Large-Scale Theorem Proving Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 10 peer-reviewed papers addressing the following research question: How does the psychometric-based evaluation method compare to traditional proof pass rate metrics in terms of accuracy and computational efficiency when applied to large-scale theorem proving. 9 claims were extracted from source literature; 2 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.8/10. This report is a mac
Machine-generated literature synthesis.